Manajemen Pembelajaran Batik untuk Mengembangkan Karakter Siswa Melalui Pendekatan Karakter di SMK Negeri 4 Palangkaraya - Ni Wayan Ratih Wahyuriani; Ni Luh Sustiawati; I Gede Mawan; I Wayan Karja (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
Effective learning management is very important to support the development of student character in Vocational High Schools (SMK). The output that is the goal of this writing is to explore the management of batik learning in SMK in an effort to instill student character values through a local wisdom approach.This study uses a case study methodology combined with a qualitative descriptive method. Analysis of learning documents, teacher and student interviews, and observations are used to collect data. The subjects of this study were grade XI students of the Batik and Textile Creative Crafts Program at SMK Negeri 4 Palangkaraya with an emphasis on batik subjects. The results of the study indicate that batik learning in SMK has the potential to develop student character, such as responsibility, patience, creativity, and love for local culture. Good learning management includes the planning, implementation, and evaluation stages that are integrated with local wisdom values. It is hoped that this approach will become a culture-based learning model that can be applied in various schools.